1998
DOI: 10.1080/02688699845348
|View full text |Cite
|
Sign up to set email alerts
|

Primary cranial Ewing's sarcoma

Abstract: Primary Ewing's sarcoma of the cranium is extremely rare, with only 17 cases reported so far. We describe a further case with involvement of the frontotemporal region and the orbit. The patient, an adult male, was admitted with headache and papilloedema, and later developed localised swelling and proptosis. He was treated with surgery, radiotherapy and chemotherapy, and was free from metastases during a follow-up of 14 months. The prognosis of Ewing's sarcoma is improving with radiotherapy and chemotherapy. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…21) Radical surgery has been advocated, 1,19,30) but these tumors are sensitive to radio-and chemotherapy, so a less aggressive approach should be considered. 2) The most common symptoms of Ewing's sarcoma are pain and swelling. The characteristic signs are low-grade fever and general malaise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21) Radical surgery has been advocated, 1,19,30) but these tumors are sensitive to radio-and chemotherapy, so a less aggressive approach should be considered. 2) The most common symptoms of Ewing's sarcoma are pain and swelling. The characteristic signs are low-grade fever and general malaise.…”
Section: Discussionmentioning
confidence: 99%
“…Only 22 cases of primary cranial Ewing's sarcomas have been reported [1][2][3]5,[8][9][10][11][12]14,[16][17][18][19]21,22,[31][32][33] in addition to a series of 14 patients with primary cranial Ewing's sarcoma. 6) Ewing's sarcoma usually occurs in the long bones of the lower limbs, generally in patients less than 15 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have consistently shown poor prognostic relationship of ES with larger size of lesion, female sex, presence of metastasis, pelvic location, high serum LDH, greater than 17 years of age, leukocyte count [7000/dl and lymphocyte count [2000/dl [1,13,27]. Radiochemotherapy followed by autologous bone marrow transplantation is a newer therapy option with promising preliminary results, especially for these high-risk patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of Ewing's sarcoma is improving with radiotherapy and chemotherapy. Further cases are needed to study the biological behaviour of primary cranial Ewing's sarcoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…Primary Ewing's sarcoma of the cranium is extremely rare, with only 17 cases reported so far [24]. Involvement of the paranasal sinus is a very rare entity.…”
mentioning
confidence: 99%